Applying Q methodology in higher teacher education for pre-service teachers’ (self-)reflection, learning and professional development - Kling, Ines; Buhl, Monika (Frontiers in education, 2025)
Reflection is as a key element in the professional development of pre-service teachers and one of the most important goals of teacher education. However, traditional reflection methods often lack the structure and effectiveness needed to foster meaningful and deep reflection. This paper highlights the need for innovative reflective approaches by investigating whether and how Q methodology can be applied to prompt pre-service teachers’ (self-)reflection in a university classroom setting. The reflection design developed combines Q-sorting with different (self-)reflective stimuli, like reviewing analysis of these sorts—based on Q-method results—and is applied in a graduate course at a university in southern Germany. The pre-service teachers engage in several occasions for self-reflection through exploration, while simultaneously receiving feedback from peers and the researcher. The paper takes the reader through the four phases of the reflection design and its findings, enabling them to envision using Q in higher teacher education for pre-service teachers’ (self-)reflection, learning and professional development. The findings show that Q is invaluable for application in a university setting with pre-service teachers: Not only are they participants, but they also use Q-sorting and its results to learn about their own teacher beliefs and attitudes, which manifest themselves through reflection and reinforces the student’ professional development. The paper also underlines the value of Q in facilitating the teachers’ continuous professionalization and engagement with topics relevant to teaching, as well as encouraging self-reflection in the teacher role.
Gesehen am 19.05.2025